Effects of Cultivar and Distillers Grains Supplementation on Grazing and Subsequent Finishing Performance of Stocker Steers Grazing Tall Fescue Pasture - L. W. Lomas; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2015)
Four hundred thirty-two yearling steers grazing tall fescue pastures were used to evaluate the effects of fescue cultivar and dried distillers grains (DDG) supplementation during the grazing phase on available forage, grazing gains, subsequent finishing gains, and carcass characteristics. Fescue cultivars evaluated were high-endophyte ‘Kentucky 31’ and low-endophyte ‘Kentucky 31,’ ‘HM4,’ and ‘MaxQ.’ Steers were either fed no supplement or were supplemented with DDG at 1.0% body weight per head daily in 2009 or 0.75% of body weight per head daily in 2010, 2011, 2012, 2013, and 2014 while grazing. Steers that grazed pastures of low-endophyte ‘Kentucky 31,’ ‘HM4,’ or ‘MaxQ’ gained significantly more (P<0.05) and produced more (P<0.05) gain/a than those that grazed high-endophyte ‘Kentucky 31’ pastures. Gains of cattle that grazed low-endophyte ‘Kentucky 31,’ ‘HM4,’ or ‘MaxQ’ were similar (P>0.05). Subsequent finishing gains were similar (P>0.05) among fescue cultivars in 2009, 2012, 2013, and 2014; however, steers that previously grazed high-endophyte ‘Kentucky 31’ had greater (P>0.05) finishing gains than those that had grazed ‘HM4’ or ‘MaxQ’ in 2010 and greater (P<0.05) finishing gains than those that grazed low-endophyte ‘Kentucky 31’ or ‘HM4’ in 2011. Supplementation of grazing steers with DDG supported a higher stocking rate and resulted in greater (P<0.05) grazing gain, gain/a, and overall daily gain and reduced the amount of fertilizer needed by providing approximately 60 lb/a, 50 lb/a, 50 lb/a, 30 lb/a, 40 lb/a, and 40 lb/a of nitrogen (N) in 2009, 2010, 2011, 2012, 2013, and 2014, respectively, primarily from urine of grazing cattle.
Keywords: tall fescue; grazing; supplementation; distillers grains